Sustainable resource governance in global production networks – challenges for human geography - Schmitt, Thomas; Schulz, Christian (ERDKUNDE, 2016)
Transnational debates, for instance on the finiteness of fossil resources and their harmful effects on the climate, are often regarded as interdisciplinary challenges in the social and natural sciences. By contrast, in the past two decades, notably in the 2000s, geography appears to have been forgetful of resources. In this paper it is argued that more attention needs to be paid to resource studies in human geography. It starts by comparing existing understandings and definitions of resources in respect of their usefulness as guiding concepts for research. This is followed by an overview of resource-related debates in various subdisciplines of geography. In (environmental) economic geography, the concept of global production networks has proved helpful for the discussion of problems connected with resources. An adaptation of this concept is presented here which can be used to analyse material and energy flows with the aid of social categories (e.g. such as power relations or governance) and to evaluate them in the light of normative categories (e.g. ecological sustainability or environmental justice).